Discontinuous Galerkin Computation of the Maxwell Eigenvalues on Simplicial Meshes - Buffa, Annalisa; Houston, Paul; Perugia, Ilaria (2005)
This paper is concerned with the discontinuous Galerkin approximation of the Maxwell eigenproblem. After reviewing the theory developed in [5], we present a set of numerical experiments which both validate the theory, and provide further insight regarding the practical performance of discontinuous Galerkin methods, particularly in the case when non-conforming meshes, characterized by the presence of hanging nodes, are employed.